2013
DOI: 10.1002/jmv.23682
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment showed no prophylactic effect in influenza virus‐infected mice

Abstract: Simvastatin, a cholesterol-lowering drug, is reported to have immunomodulatory properties that attenuated acute lung injury independent of their major lipid lowering effects. Based on these reports, simvastatin is expected to be used for influenza prophylaxis and treatment. The present study evaluated the efficacy of simvastatin against influenza A/PR/8/34 virus infection in a murine model. In a first study, simvastatin was administered orally. To achieve high plasma levels, intraperitoneal application was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…1), treatment of BL6 mice with statins prior to and during acute MHV68 infection did not attenuate MHV68 replication but, instead, produced a mild delay in the clearance of infectious virus. These results are in agreement with similar findings in the influenza virus system, where the clearly delineated antiviral effects of statins in vitro failed to manifest in influenza virus-infected wild-type mice (20,21). In contrast, treatment of IFNAR1 Ϫ/Ϫ mice with statins dramatically reduced acute MHV68 replication in the lungs, supporting the model where MHV68 usurps type I IFN signaling to overcome the antiviral effects of statins.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1), treatment of BL6 mice with statins prior to and during acute MHV68 infection did not attenuate MHV68 replication but, instead, produced a mild delay in the clearance of infectious virus. These results are in agreement with similar findings in the influenza virus system, where the clearly delineated antiviral effects of statins in vitro failed to manifest in influenza virus-infected wild-type mice (20,21). In contrast, treatment of IFNAR1 Ϫ/Ϫ mice with statins dramatically reduced acute MHV68 replication in the lungs, supporting the model where MHV68 usurps type I IFN signaling to overcome the antiviral effects of statins.…”
Section: Discussionsupporting
confidence: 90%
“…For some viruses (i.e., respiratory syncytial virus and hepatitis C virus), statins decrease viral replication both in vitro and in vivo (5,18,19). In contrast, in spite of the antiviral effects of statins on influenza virus replication in tissue culture, treatment of influenza virus-infected mice with statins either has no effect on viral replication, clearance, and lung pa-thology or actually decreases survival rates (20)(21)(22). Interestingly, statin treatment of older hospitalized patients suffering from seasonal influenza correlates with improved overall survival; however, the factors directing improved survival are not known (23).…”
mentioning
confidence: 99%
“…It has been shown to reduce lung inflammation in mouse models of airway injury (3134) and bacterial infections (3537). However, simvastatin was not shown to have a significant effect on influenza A virus pathogenesis in mice (3840). Besides rosiglitazone and simvastatin, mainly immunomodulatory drugs were predicted to have inhibitory effects on pathological host responses to A/Anhui/1/2013 infection.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, statins have been examined in murine models of influenza A pneumonia. Collectively, it has been shown that several statins have no significant effect on viral clearance, lung injury, weight loss, or mortality [169], although one group found reduced survival in simvastatin-treated mice [170]. …”
Section: A Role For Statins In Host Defense?mentioning
confidence: 99%